The "Learning Disabilities-to-Prison" Pipeline: evidence From the Add Health National Longitudinal Study - Mallett, Christopher A. (Crime & delinquency, 2023)
Young people with learning disabilities, and in particular those of color, are significantly more at risk for having school difficulties, delinquency, and incarceration. The National Longitudinal Study of Adolescent to Adult Health (Add Health) data were used to investigate how learning disabilities, school experiences, gender, and race impacted delinquency and criminal activity and incarceration?looking at a learning disabilities-to-prison link. Structural equation modeling was used to analyze the relationship between measured variables and latent constructs, comparing those young people with learning disabilities and those without. It was found that these pathways are quite complicated to discern; reflecting the current knowledge of this ?learning disabilities pipeline? hypothesis. For young people with learning disabilities compared to young people without learning disabilities, juvenile delinquency was more likely if the young person was male or Hispanic; criminal activities were more likely for Black children and for those delinquent or incarcerated as a juvenile; and females were less likely to be incarcerated as an adult, but school dropouts, Black children, and those incarcerated as a juvenile were more likely. Implications are set forth, as well as recommendations to stakeholders.